“Positive Relationships” and their impact on wellbeing: A review of current literature - Mertika, Antigoni; Mitskidou, Paschalia; Stalikas, Anastassios (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Positive relationships are widely considered to be one of the pillars of well-being. Their boosting effect on emotional and physical health has repeatedly been documented by experimental and longitudinal studies. Despite their instrumental role, the existing literature does not offer systematic observations of their nature and characteristics. In this paper, we aim to explore the specific characteristics of positive relationships. We conducted a thorough research of the existing most recent literature and grouped our findings according to the following two research questions: (a) the kind of relationships that are positive in people’s lives and, (b) the way positive relationships relate and support well-being. Our findings suggested that specific relationships are examined with respect to different age groups, e.g. peer relationships in adolescence or marital relationships in adulthood. All relationships described as positive at each developmental stage are correlated with wellbeing in various ways. Beyond the characteristics of people and the way they relate, relationships seem to contribute to wellbeing by sharing positive moments and events, being supportive with respect to autonomy and showing an attitude of interest and emotional engagement. In conclusion, we argue that while relationships seem to contribute to wellbeing, there is not yet an exhaustive list of ingredients that make the relationship “positive”. We suggest new ways to enhance the study of positive relationships as well as possible variables that have not yet been examined and could possibly enhance our understanding of positive relationships and their influence on wellbeing.